2013
DOI: 10.1101/lm.030007.112
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced noradrenergic activity potentiates fear memory consolidation and reconsolidation by differentially recruiting α1- and β-adrenergic receptors

Abstract: Consolidation and reconsolidation are phases of memory stabilization that diverge slightly. Noradrenaline is known to influence both processes, but the relative contribution of a1-and b-adrenoceptors is unclear. The present study sought to investigate this matter by comparing their recruitment to consolidate and/or reconsolidate a contextual fear memory trace under enhanced noradrenergic activity induced by yohimbine. We report that this a2-adrenoceptor antagonist was able to potentiate fear memory trace conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 74 publications
11
78
0
Order By: Relevance
“…Studies have shown that blocking β-adrenergic transmission by propranolol impairs memory reconsolidation in auditory fear conditioning, spatial radial maze, and cocaine-induced CPP (12,(26)(27)(28)(29)(30); inhibition of basal and stimulated activities of certain components of G protein-coupled pathways associated with neuroplasticity, such as PKA, ERK, and CREB, disrupts reconsolidation of fear and object recognition memories (31)(32)(33)(34). In cocaine-associated reward memory task, bilateral intraamygdalar infusions of the PKA inhibitor Rp-cAMPS following light/tone stimulus reactivation decreases subsequent cue-induced reward memory reconsolidation (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that blocking β-adrenergic transmission by propranolol impairs memory reconsolidation in auditory fear conditioning, spatial radial maze, and cocaine-induced CPP (12,(26)(27)(28)(29)(30); inhibition of basal and stimulated activities of certain components of G protein-coupled pathways associated with neuroplasticity, such as PKA, ERK, and CREB, disrupts reconsolidation of fear and object recognition memories (31)(32)(33)(34). In cocaine-associated reward memory task, bilateral intraamygdalar infusions of the PKA inhibitor Rp-cAMPS following light/tone stimulus reactivation decreases subsequent cue-induced reward memory reconsolidation (35).…”
Section: Discussionmentioning
confidence: 99%
“…In therapeutic contexts, disrupting the process of reconsolidation could change or erase pathophysiological memories (28,30,38). Blockade of β-AR signaling disrupts reconsolidation of memory for learned behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stress-induced activation of the HPA axis involves the synthesis and secretion of glucocorticoids (cortisol in humans and corticosterone in most rodents) from the adrenal cortex (8). Both animal and human studies have shown that these stress hormones have profound effects on cognition by acting on specific brain regions involved in the processing of emotional stimuli (1,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Noradrenaline is associated with memory processing as it induces lasting changes in the brain that could sustain memories over time (Gazarini et al, 2013). As confirmed later on its neurotransmission indeed strengthens memory-related synaptic plasticity such as long-term potentiation, allowing memories to be formed and maintained in a more intense and enduring manner, a notion particularly valid for those with emotional content (Joëls et al, 2011).…”
Section: Role Of Other Neurotransmittersmentioning
confidence: 92%
“…Like other types of memory, an emotional memory has to be consolidated to allow its later retrieval. Accumulating evidence has indicated that noradrenaline acts during these gradual stages to finetune the strength and/or persistence of a memory (Guzmán-Ramos, 2012; Gazarini et al, 2013).…”
Section: Role Of Other Neurotransmittersmentioning
confidence: 99%